2009
DOI: 10.1128/aac.00064-09
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Ertapenem into a Hospital Formulary: Effect on Antimicrobial Usage and Improved In Vitro Susceptibility of Pseudomonas aeruginosa

Abstract: After ertapenem was added to the formulary of a 344-bed community teaching hospital, we retrospectively studied its effect on antimicrobial utilization and on the in vitro susceptibility of various antimicrobial agents against Pseudomonas aeruginosa. Three study periods were defined as preintroduction (months 1 to 9), postintroduction but before the autosubstitution of ertapenem for ampicillin-sulbactam (months 10 to 18), and after the policy of autosubstitution (months 19 to 48) was initiated. Ertapenem usage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
42
5
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 20 publications
1
42
5
1
Order By: Relevance
“…In contrast to findings of previous studies in Pseudomonas aeruginosa (12,24,25), we found that ertapenem consumption was associated with a rise in CRAB prevalence. Ertapenem is presumed to have a lower potential to induce resistance in P. aeruginosa or A. baumannii, given the intrinsic resistance in both organisms.…”
Section: Discussioncontrasting
confidence: 57%
“…In contrast to findings of previous studies in Pseudomonas aeruginosa (12,24,25), we found that ertapenem consumption was associated with a rise in CRAB prevalence. Ertapenem is presumed to have a lower potential to induce resistance in P. aeruginosa or A. baumannii, given the intrinsic resistance in both organisms.…”
Section: Discussioncontrasting
confidence: 57%
“…In a long-term study, despite an increasing use of ertapenem over a 9 year period, no association was found between ertapenem and changes in pseudomonal susceptibility to carbapenems [37]. Other studies have reported an increased susceptibility to imipenem among P. aeruginosa after introduction of ertapenem, presumptively due to decrease in group 2 carbapenems [35,36]. While the present study detected an overall decrease in carbapenem non-susceptible Pseudomonas isolates in the postintervention period, whether this is a direct impact of ertapenem or through indirect changes in other antimicrobials is unknown.…”
Section: Discussionmentioning
confidence: 92%
“…[35][36][37]. In many instances, these investigations reported improved susceptibilities of Enterobacteriaceae and Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 97%
“…15 Goldstein et al reported that adding ertapenem to the formulary in a 344-bed community hospital was an effective antimicrobial management tool. 7 Apisarnthanarak et al demonstrated that conducting surveillance and implementing prescribing policies resulted in reductions in antibiotic consumption and resistance in a tertiary care hospital in a developing country.…”
Section: Discussionmentioning
confidence: 99%